Penerapan Penggunaan Aplikasi Digital Kasir Pada Pelaku Umkm Warung Mba Merry - Grace Orlyn Sitompul; Petersina Fatrisya Eleuwyaan; Patricia Rosmawati; Naomi Refina Siahaan; Mutiara Br Hotang; Novi Manurung (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Micro, Small, and Medium Enterprises (MSMEs) are one of the main pillars of Indonesia's economy. However, they often face managerial and financial inefficiencies, especially in manual transaction recording. This community service project focuses on the digitalization of transaction systems through the implementation of the PosSaku cashier application at Warung Mba Merry, a culinary MSME in West Bandung. The method used includes interviews, observations, literature studies, and hands-on practice. The project aims to improve transaction recording efficiency, inventory management, and financial reporting. The application not only facilitates transaction tracking but also offers business training and a community platform. The results showed increased transaction speed, accuracy in financial data, and more structured cash flow monitoring. Although some technical obstacles were found, such as device limitations and internet connectivity, overall, the implementation was successful. This digital solution proves to be effective in helping MSMEs adapt to technology and improve business professionalism and competitiveness.